2015
DOI: 10.1080/07929978.2014.895561
|View full text |Cite
|
Sign up to set email alerts
|

Fruit trees’ survival ability in an arid desert environment without irrigation in the Negev Highlands of Southern Israel

Abstract: More than a hundred abandoned but presently maintained fruit trees are scattered in the Negev Desert Highlands in Southern Israel. Most of the older groves were planted by Bedouins in pre-existing agricultural systems built in the distant past, mainly during the Byzantine era, mostly during the sixth and seventh centuries AD. In these groves a variety of domesticated fruit trees such as date palms, figs, pomegranates, almonds, carobs, pistachios, bitter oranges, grapevines and olives have been planted. The tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Furthermore, in extreme floods, runoff harvested in these terraces would be protected from becoming drained to the downstream Wadi Shaharut. Structural characteristics of these terraces are similar to those of many agricultural runoff harvesting infrastructures that were located in many ephemeral stream channels across southern Israel and dated to the Byzantine Age (fourth to seventh century AD) [21][22][23]. As elsewhere, agricultural utilization of Byzantine runoff harvesting infrastructures during later ages is very probable [22,23].…”
Section: Indicators Of Ancient To Recent-past Runoff Agriculturementioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, in extreme floods, runoff harvested in these terraces would be protected from becoming drained to the downstream Wadi Shaharut. Structural characteristics of these terraces are similar to those of many agricultural runoff harvesting infrastructures that were located in many ephemeral stream channels across southern Israel and dated to the Byzantine Age (fourth to seventh century AD) [21][22][23]. As elsewhere, agricultural utilization of Byzantine runoff harvesting infrastructures during later ages is very probable [22,23].…”
Section: Indicators Of Ancient To Recent-past Runoff Agriculturementioning
confidence: 66%
“…Structural characteristics of these terraces are similar to those of many agricultural runoff harvesting infrastructures that were located in many ephemeral stream channels across southern Israel and dated to the Byzantine Age (fourth to seventh century AD) [21][22][23]. As elsewhere, agricultural utilization of Byzantine runoff harvesting infrastructures during later ages is very probable [22,23]. For example, evidence for modern agricultural land use was provided for terraced lands in some wadis across the central Arava Valley by the location of tillage-induced shallow soil furrows, which indicate recent (decades old) tillage by Bedouins [24].…”
Section: Indicators Of Ancient To Recent-past Runoff Agriculturementioning
confidence: 77%
“…When these run-off systems were active, the landscape would have included tens to hundreds of orchards and vineyards, and been totally different from the current landscape. As Ashkenazi et al, (2015) found in the Negev Highlands, more than a hundred fruit trees planted by Bedouin in the early 20 th century survive without any human maintenance thanks to water that accumulates from old runoff harvesting systems.…”
Section: Fig 4: Agricultural Terraces In the Judean Mountainsmentioning
confidence: 99%
“…The fact that most of the agricultural installations are restricted to the location of the present best runoff generation units may suggest that there was no significant change in the environmental conditions observed since these installations were built, some 1600 years ago. Recent study (Ashkenazi et al, 2014) indicates that after the 10 th century, the semi-nomad Bedouin population almost constantly practiced desert agriculture on a local scale in the Negev Highlands. This indicates that todays' desert climate and environment are suitable for desert agriculture practices, and that the desert environment in the southern Levant was almost unchanged at least during the last two millennia.…”
Section: Environmental Implications: Compiling the Results Of The Botmentioning
confidence: 99%